Eco-physiological characterization of the macroinverterbate communities of an urban stream (Rio Tinto, Portugal) - Jesus, Teresa Maria Gonçalves Moreira de (2019)
The Water Framework Directive ( DQA-2000/60/EC ) establishes as its main objective the achievement of a good ecological quality of all inland surface waters and groundwater by 2015 , and introduces the concept of " ecological status " of an ecosystem , which includes the study of a wide range of parameters and factors for determining the " health " system ". This work, carried out within a project which main objective is the rehabilitation of a small watercourse in high degree of ecological degradation, aims to make the study of benthic macroinvertebrate communities and some parameters related to the ecological state of Rio Tinto (Douro watershed) in order to determine the main sources of pollution and to propose measures for its rehabilitation. This study compare results (metrics and functional structure) of samples of the benthic macroinvertebrate communities collected at 10 sampling sites along the river in 2013/14 and values of some hydro-morphological, physical and chemical parameters. The results indicate that it is a water course which presents a high degree of degradation due to problems with artificiality of the channel and receipt of domestic and industrial effluents.